A Two-Wired Ultra-High Input Impedance Active Electrode - Guerrero, Federico Nicolás (2018)
This paper presents a novel two-wired active electrode that achieves ultrahigh input impedance using power supply bootstrapping. The proposed circuit reduces the input capacitance of a buffer amplifier while enabling measurements using leads with only two wires, providing a low-complexity and low-cost solution for interference rejection and artifact reduction in dc-coupled dry-contact biopotential measurements. An implemented prototype shows that, even using standard operational amplifiers, an input capacitance as low as 71 fF can be obtained, maintaining a high impedance in a 0-1 kHz bandwidth, sufficient for ECG, EEG, and EMG measurements. The circuit has a simple and easily replicable implementation that requires no individual adjustment. A common mode rejection ratio (CMRR) above 103 dB at 50 Hz was achieved and the increased rejection to interference due to the potential divider effect was experimentally tested maintaining a 92-dB CMRR at 50 Hz with a 1.2-M Ω source impedance unbalance. ECG measurements were conducted to validate the active electrode against a traditional alternative, and a test with dry-contact EEG electrodes was successfully conducted. Although the proposed circuit is intended to acquire superficial electrophysiological signals using dry electrodes, it can be used for measurement from other high-impedance sources, such as micropipette electrodes.